KEBUDAYAAN MANUSIA PRASEJARAH DI DESA TANJUNG ARO SEBAGAI SUMBER PEMBELAJARAN SEJARAH - Zeheskiel Edo Ardianza (Universitas Negeri Surabaya, 2017)
Culture is as a result of the work, taste and creation of society. Community work produces material and material culture or physical culture (material culture) needed by humans to control the natural surroundings, so that the strength and the results can be devoted to the needs of the community. Based on this, the problem in this study is how prehistoric human culture in Tanjung Aro village , North Pagaralam City. The purpose of this study is as an effort to look at cultural relics whose use still shows megalithic traditions, namely the worship of ancestral spirits. The research method used is descriptive qualitative method, which uses how to collect data sources systematically and use data sources in depth. This study uses three ways in data collection namely observation, interviews, documents. The results of this study indicate that there are some megalithic remains such as dolmen, megalithic statues, stone chambers, stone mortars, tetraliths which are used as a medium of worship for certain rituals by the community until now.Keywords: Culture, Megalithic, Prehistoric Man.